Baseline Results of the West London lung cancer screening pilot study – Impact of mobile scanners and dual risk model utilisation. (October 2020) - Bartlett, Emily C.; Kemp, Samuel V.; Ridge, Carole A.; Desai, Sujal R.; Mirsadraee, Saeed; Morjaria, Jaymin B.; Shah, Pallav L.; Popat, Sanjay; Nicholson, Andrew G.; Rice, Alexandra J.; Jordan, Simon; Begum, Sofina; et al.
Highlights: No difference was found in uptake for lung cancer screening at a mobile vs fixed site. Scanner location was felt to be the "right place for a scan" for >95 % of attendees at both sites. Risk based selection of participants resulted in a prevalence of lung cancer of 2.5 %. 5/29 of those with lung cancer were not eligible for a scan according to the PLCOM2012 model. All participants with lung cancer qualified for a scan using the LLPv2 risk model. Abstract: Objectives: The West London lung screening pilot aimed to identify early-stage lung cancer by targeting low-dose CT (LDCT) to high risk participants. Successful implementation of screening requires maximising participant uptake and identifying those at highest risk. As well as reporting pre-specified baseline screening metrics, additional objectives were to 1) compare participant uptake between a mobile and hospital-based CT scanner and 2) evaluate the impact on cancer detection using two lung cancer risk models. Methods: From primary care records, ever-smokers aged 60–75 were invited to a lung health check at a hospital or mobile site. Participants with PLCOM2012 6-yr risk ≥1.51 % and/or LLPv2 5-yr risk ≥2.0 % were offered a LDCT. Lung cancer detection rate, stage, and recall rates are reported. Participant uptake was compared at both sites (chi-squared test). LDCT eligibility and cancer detection rate were compared between those recruited under each risk model. Results: Of 8366 potential participants invited, 1047/5135 (20.4 %) invitees responded to an invitation to the hospital site, and 702/3231 (21.7 %) to the mobile site (p = 0.14). The median distance travelled to the hospital site was less than to the mobile site (3.3 km vs 6.4 km, p < 0.01). Of 1159 participants eligible for a scan, 451/1159 (38.9 %) had a LLPv2 ≥2.0 % only, 71/1159 (6.1 %) had a PLCOM2012 ≥1.5 % only; 637/1159 (55.0 %) met both risk thresholds. Recall rate was 15.9 %. Lung cancer was detected in 29/1145 (2.5 %) participants scanned (stage 1, 58.6 %); 5/29 participants with lung cancer did not meet a PLCOM2012 threshold of ≥1.51 %; all had a LLPv2 ≥2.0 %. Conclusion: Targeted screening is effective in detecting early-stage lung cancer. Similar levels of participant uptake at a mobile and fixed site scanner were demonstrated, indicating that uptake was driven by factors in addition to scanner location. The LLPv2 model was more permissive; recruitment with PLCOM2012 alone would have missed several cancers.